2023
DOI: 10.3390/vaccines11081308
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Porcine Circovirus Infection: Recent Insights and Its Significance in the Piggery Sector

Hemanta Maity,
Kartik Samanta,
Rajib Deb
et al.

Abstract: Porcine circovirus (PCV), a member of the Circoviridae family within the genus Circovirus, poses a significant economic risk to the global swine industry. PCV2, which has nine identified genotypes (a–i), has emerged as the predominant genotype worldwide, particularly PCV2d. PCV2 has been commonly found in both domestic pigs and wild boars, and sporadically in non-porcine animals. The virus spreads among swine populations through horizontal and vertical transmission routes. Despite the availability of commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 307 publications
0
6
0
Order By: Relevance
“…Porcine circovirus (PCV), belonging to the family Circoviridae in the genus Circovirus , imposes significant economic losses on the global pig farming industry . PCV is a small, icosahedral, nonenveloped, circular single-stranded DNA virus with a diameter ranging from 13 and 25 nm , and is responsible for porcine circovirus virus-associated diseases (PCVAD), such as porcine dermatitis and nephropathy syndrome, postweaning multisystemic wasting syndrome (PMWS), reproductive failure, acute pulmonary edema, porcine respiratory disease complex and granulomatous enteritis. There are currently four recognized types: PCV1 to PCV4 (Figure C), with PCV1 generally considered nonpathogenic . In contrast, PCV2 is an important causative agent of PCVAD.…”
Section: Different Origins Of Cssdnamentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine circovirus (PCV), belonging to the family Circoviridae in the genus Circovirus , imposes significant economic losses on the global pig farming industry . PCV is a small, icosahedral, nonenveloped, circular single-stranded DNA virus with a diameter ranging from 13 and 25 nm , and is responsible for porcine circovirus virus-associated diseases (PCVAD), such as porcine dermatitis and nephropathy syndrome, postweaning multisystemic wasting syndrome (PMWS), reproductive failure, acute pulmonary edema, porcine respiratory disease complex and granulomatous enteritis. There are currently four recognized types: PCV1 to PCV4 (Figure C), with PCV1 generally considered nonpathogenic . In contrast, PCV2 is an important causative agent of PCVAD.…”
Section: Different Origins Of Cssdnamentioning
confidence: 99%
“…48−52 There are currently four recognized types: PCV1 to PCV4 (Figure 1C), with PCV1 generally considered nonpathogenic. 46 In contrast, PCV2 is an important causative agent of PCVAD. When compared with other known singlestranded DNA viruses, it exhibits the highest rate of nucleotide substitutions.…”
Section: Cssdna As Bacteriophage and Virus Genomesmentioning
confidence: 99%
“…When comparing the amino acid sequences of Cap proteins from PCV subtypes 1–4, the homology ranges from 24.5 to 64% ( 7 , 9 ). Since the significant antigenic response and the lower genetic relatedness of ORF2, it can be used for detecting and distinguishing different subtypes of PCV ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although different experimental and field studies have demonstrated the performance of PCV-2 vaccines reducing viremia, clinical signs and/or microscopic lesions in presence of MDA, a proportion of pigs may still develop PCV-2-SI [ 16 19 ]. Importantly, the percentage of early infections depends on the balance between the level of MDI and the infectious pressure existing on a particular farm and batch, as well as co-infections with different pathogens [ 20 ]. The intensification of the swine industry in the last three decades has favoured more complex clinical presentations due to co-infections, with PCV-2 being found alongside porcine reproductive and respiratory syndrome virus (PRRSV), porcine parvovirus 1, and Mycoplasma hyopneumoniae , among others [ 21 ].…”
Section: Introductionmentioning
confidence: 99%